water detection on the ground subsurface using electromagnetic device EM-34 for Airport Runaway. - Omar, Husaini; Md Yusoff, Zainuddin; Mohd Pauzi, Nur Irfah; Khalit, Saiful Iskandar; Nasib, Mohd Yunus (2011)
Sepang area which was underlain by problematic soil such as peat soil and clay has become a major problem for constructing airplane runaway. The differential settlement which results from water ponding creates major problem in laying the pavement for airplane runaway. This project is to detect the water ponding below the ground surface using electromagnetic device EM-34. EM-34 is a two man portable device, has a capability to survey from 7.5 meters to a maximum of 60 meters. The two coils flexibly connected is used to measure electronically so that the receiver operator simply reads a meter to accurately set the coils to the correct spacing, which can be 10, 20 or 40 meters. The electrical conductivity could detect the soil or rock material as the electric current can be made flow through it. The electromagnetic device could detect the water in soil which was the main objectives for this project. In conclusion, the CH 15 + 200 until CH 16 + 700 at depth 7.5 meters have been detected with water but mostly as soil water as indicated in Figure 5 and Figure 6. In addition, the CH 15 + 200 until CH 16 + 700 have been interpreted as clay and wet clay layers at the depth of 15 meters